Manajemen Risiko Berbasis Budaya: Peran Nilai-Nilai Bali dalam Penguatan Akuntabilitas LPD - Wulandari, Dewa Ayu Eny (Journal of Principles Management and Business, 2025)
This study aims to analyze the implementation of risk management in Rural Credit Institutions using a framework based on local cultural values.This study used a qualitative descriptive method with informants from managers and supervisors of the LPD Desa Adat Bualu. The implementation of risk management in LPD Desa Adat Bualu based on the five dimensions of the COSO framework was applied to realise the Catur Purusha Artha values. In addition, Tri Hita Karana crystallises in the behavioural patterns of all LPD management and supervisors to carry out internal control. The internal control system still needs to be improved in documenting risk identification and risk analysis, so that performance information carried out by management is conveyed to the village community as the principal. In addition, the internal supervisory side collaborates with independent supervisors to increase trust in management performance. This study supports the concept of agency theory, as implementing risk management and creating an internal control system can avoid information asymmetry and conflicts of interest between LPD management and the traditional village community as the owners of funds in LPD. The implication of risk management policies in LPDs is that they need to be adjusted to the characteristics of LPDs that use local cultural values. This study presents a combination of Balinese local values  within the five dimensions of the COSO framework. However, efforts from internal control carried out by LPD management can also become information asymmetry when there are differences in risk assessment and risk control perspectives from internal supervisors. Therefore, there needs to be awareness to improve individual competence from both LPD managers and LPD supervisors, especially in the financial sector.